Trust, stigma reduction, and quality of life in obesity mHealth adoption - Alfarizi, Muhammad; Arifian, Rafialdo (Universitas Pendidikan Nasional, 2026)
The rapid growth of mobile health (mHealth) technologies has transformed obesity management in emerging markets, including Indonesia, where rising obesity prevalence coincides with high smartphone penetration. Despite the increasing availability of digital obesity care applications, limited research has examined adoption from a consumer decision-making perspective. This study investigates how Digital Self-Management Capability and Perceived Ethical Digital Health Marketing influence Adoption and Continuance Intention of obesity mHealth services, through the mediating roles of Quality of Life Improvement and Consumer Trust, as well as the impact of Obesity Stigma Reduction. Using a quantitative cross-sectional survey design, data were collected from 379 Indonesian adults with overweight or obesity who had experience using digital obesity management applications. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Digital Self-Management Capability significantly enhances Quality of Life Improvement, strengthens Consumer Trust, and substantially reduces perceived Obesity Stigma. Perceived Ethical Digital Health Marketing significantly improves Quality of Life and Consumer Trust, but does not directly reduce stigma. Furthermore, Quality of Life Improvement, Consumer Trust, and Obesity Stigma Reduction all significantly influence Adoption and Continuance Intention, with Consumer Trust emerging as the strongest predictor. The study contributes theoretically by integrating motivational, relational, and psychosocial mechanisms into a value-based consumer adoption model for digital obesity care. In practice, the findings highlight that the sustainable adoption of obesity mHealth services in Indonesia depends not only on technological functionality but also on building trust, reducing stigma, and delivering meaningful improvements in users’ quality of life.